Primary school children's beliefs associating extra-curricular provision with non-cognitive skills and academic achievement. Issue 1 (2nd January 2020) - Murray, Jane; Cousens, David
ABSTRACT: This article focuses on the beliefs of primary school children aged 7–11 years in England concerning the impact of adult-led after-school extended provision (EP) on their development of non-cognitive skills (NCS). In responses to a questionnaire survey and focus group interviews, children were more positive than parents, teachers and school governors, believing EP enabled them to acquire numerous NCS, including most emotional intelligence competences, but excluding social skills related to locus of control. Findings support the argument that EP affording NCS development may enhance academic achievement, indicating that NCS development embedded in primary curricula may also benefit academic achievement.